2022
DOI: 10.1021/acsomega.1c05859
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Ultrathin Mixed-Phase Ga2O3Films Grown on the α-Al2O3Substrate via Mist-CVD

Abstract: Alpha (α)- and beta (β)-phase gallium oxide (Ga2O3), emerging as ultrawide-band gap semiconductors, have been paid a great deal of attention in optoelectronics and high-performance power semiconductor devices owing to their ultrawide band gap ranging from 4.4 to 5.3 eV. The hot-wall mist chemical vapor deposition (mist-CVD) method has been shown to be effective for the growth of pure α- and β-phase Ga2O3 thin films on the α-Al2O3 substrate. However, challenges to preserve their intrinsic properties at a critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…In Figure b, TEM images show the ultrathin Ga 2 O 3 film obtained in 5 to 6 nm with a growth rate of 0.041 nm/min. Our previous study showed the 20 nm thin mixed-phase Ga 2 O 3 film grown on the sapphire substrate at 470 to 600 °C . In this study, we achieved an ultrathin (5 nm) film of the pure β phase at 700 °C, but this phase transition does not correlate with thickness.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…In Figure b, TEM images show the ultrathin Ga 2 O 3 film obtained in 5 to 6 nm with a growth rate of 0.041 nm/min. Our previous study showed the 20 nm thin mixed-phase Ga 2 O 3 film grown on the sapphire substrate at 470 to 600 °C . In this study, we achieved an ultrathin (5 nm) film of the pure β phase at 700 °C, but this phase transition does not correlate with thickness.…”
Section: Resultsmentioning
confidence: 71%
“…Our previous study showed the 20 nm thin mixed-phase Ga 2 O 3 film grown on the sapphire substrate at 470 to 600 °C. 28 In this study, we achieved an ultrathin (5 nm) film of the pure β phase at 700 °C, but this phase transition does not correlate with thickness. This indicates that the growth rate is much slower in this mist CVD growth process.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Gallium oxide (Ga 2 O 3 ) with an ultrawide band gap (UWBG) has piqued the interest of researchers working on deep ultraviolet (UV) photonics and next-generation power electronic devices. Semiconductors based on UWBG Ga 2 O 3 materials can withstand much higher critical electric fields (6–8 MV/cm) before avalanche breakdown than silicon- (Si), silicon carbide- (SiC), and gallium nitride (GaN)-based devices. ,, Furthermore, Baliga’s figure of merit presents the advantage of Ga 2 O 3 for power switching applications over the Si (3000×), SiC (10×), and GaN (4×). , It has been demonstrated that high-quality single-crystal Ga 2 O 3 can be synthesized using melt growth techniques such as Czochralski, floating zone, and edge-defined film-fed growth (EFG). In addition, halide vapor phase epitaxy (HVPE), molecular beam epitaxy (MBE), and chemical vapor deposition (CVD) methods for growing high-quality Ga 2 O 3 have been developed. Johnson’s figure of merit (JFOM/power–frequency product) of Ga 2 O 3 (3× of GaN) , illustrates the potential benefit of using Ga 2 O 3 in radio frequency (RF) devices. Chabak et al have reported on the fabrication of the Ga 2 O 3 MOSFET device using a thin and highly doped channel and achieving a drain-source current of 275 mA/mm at a drain to source bias of 10 V for that exhibited record-high f t / f max = 5.1/17.1 GHz .…”
Section: Introductionmentioning
confidence: 99%
“…The heterojunction and Schottky junction-based β-Ga 2 O 3 devices are of great interest for the development of high-voltage devices and solar-blind UV photodetectors, considering the intrinsic n-type conductivity of β-Ga 2 O 3 in the presence of unintentional dopants. The conventional Ga 2 O 3 Schottky junction devices were studied with metal electrodes such as Au, Pt, and Ni, taking into account the metals’ appropriate work function. , Again, studies on metal–insulator–semiconductor (MIS)-based SBD devices have been conducted, owing to the benefit of lowering the reverse saturation current. The MIS-based SBD devices have been fabricated using insulating dielectric materials, such as SiO 2 , Si 3 N 4 , Al 2 O 3, and so forth. , The thermal stability of Ga 2 O 3 Schottky contacts is also an important aspect, for which materials with high melting temperatures and low reactivity with Ga 2 O 3 are of significant interest . Furthermore, controlling near-surface ion damage during sputtering deposition of a barrier layer/insulating dielectric , is required.…”
Section: Introductionmentioning
confidence: 99%